Reflections from Learners of English as a Foreign Language in a Multicultural Non-native Context - KİMSESİZ, Fatma (LPPM Universitas Advent Indonesia, 2024)
This paper aims to reflect the ideas of learners of English at higher education level in a multicultural non-native context. The participants were six learners of English (N=6) from six different countries and they were in the preparatory English class to major in the Department of International Affairs at a state university in Turkey. The design of the study was maintained through in-depth interviews with the participants selected through a convenient snowball sampling. The data was documented in a descriptive form. The main findings elicited that although it would be better and more effective if they learned English in a native context, participants were all satisfied to learn English in a multicultural classroom which may provide some advantages in terms of learning different things and thinking in a multicultural environment. The motivation that drove them to learn English in a non-native environment was commonly related to educational reasons, yet they also indicated that they enjoyed learning foreign languages. In addition, the study submits that although it may sound favourable to learn English in its native context by native speaker language teachers, placing greater emphasis on hard work and effort, it is also attainable to learn English in a non-native context by non-native speaker teachers.